Local health traditions : plurality and marginality in South Asia - Mishra, Arima(ed.); Mishra, Arima (Hyderabad Orient Blackswan Private Limited, 2019)
With a special reference to India.
Contributed articles.
Includes bibliographical references and index.
Keywords: Traditional medicine; Healing; Women healers